(untitled) (Academic Journal of Internal Affairs, 2011)
The article, written by the Deputy-Minister for Internal Affairs, focuses on the relationship between politics and science, and uses the case study of municipal police. Examples from legislative endeavours in the past decade are used to demonstrate the complex interrelation of governance and science.